Que signifient les mots « public », « corps public », « bureau public » et « corps politique » utilisés aux articles 33, 828, 838 et 844 du Code de procédure civile du Québec ? - Reid, Hubert (Les Cahiers de droit, 1977)
In the province of Quebec, as elsewhere in Canada, the legislator, authors and judges frequently use terms in a general sense which is always taken for granted. But when the exact meaning of such terms is sought, no useful definition can be found. « Public », « public body », « public board » and « body politic » are typical examples of such terms. The purpose of this paper is to search for the legal signification of these four terms, more particularly in the United States and in Great Britain where they have been analyzed.